High level review of the Optimum Water Use methodology for agriculture following the 2018 drought in England - Knox, Jerry W.; Hess, Tim M. (Cranfield University, 2019)
1. Context. After a spate of relatively average to ‘wet’ summers in England from an irrigation perspective, the heatwave and protracted dry conditions in 2018 highlighted the significant agronomic and economic importance of water resources for agricultural irrigation and the risks to production that can arise when abstractions are restricted. From an abstraction licensing perspective (licensed volume and reasonable need) 2018 also provides a useful ‘reference’ year against which actual irrigation applications (depths applied) can be compared against theoretical ‘design’ dry year requirements. It also offers an opportunity to gather feedback from abstractors on their management practices, how they coped with the drought conditions and any lessons learnt in order to support the EA in providing abstractor guidance to support improved decision-making in future drought years. Following discussion with EA staff, this short study was commissioned to produce a Technical Briefing Note for the irrigated agriculture sector in England ahead of the 2019 spray irrigation season. The intention was that the report would include a brief agroclimatic assessment of 2018 and provide additional information to complement the EA Spray Irrigation (SI) Prospects Information which is distributed to abstractors each year. This Technical Briefing Note summarises the aim and objectives of the study, the methodological approaches developed and the key findings that emerged from the analyses.